PENGEMBANGAN MEDIA AUDIO VISUAL SEBAGAI MEDIA DALAM MENINGKATKAN AKTIVITAS FISIK USIA 20-30 TAHUN DI MASA PANDEMI COVID-19 (Jurnal Kesehatan Siliwangi, 2021)
The Strategic Plan of the Ministry of Health 2020-2024 stipulates that the three strategic targets for health promotion and community empowerment are reducing the number of people who do less physical activity (150 minutes per week) from 33.5% to 30% (RPJM Kesehatan 2020-2024). The purpose of this research was to develop a physical activity media audiovisual and looking the impact of improving physical activity for citizens aged 20-30 on the COVID-19 pandemic in Margajaya village, Bandung Barat. This research used the ADDIE method to developing media and quasi-experimental one-group pretest-posttest to measure the effectiveness of media. This research involves one person of material expert, one person of media expert, 5 citizens aged 20 – 30 as a small group test, and 31 citizens aged 20-30 in RW 06 Margajaya Village, Bandung Barat as subject group test. Data was taken by online platform from Whatsapp messenger and google form, after that data on processing and analyzing with Wilcoxon test using spss application. The univariate analysis result showed an average of physical activity value before using audiovisual media is 597,87 MET and physical activity value after using audiovisual media is 714,15 MET. The bivariate analysis result showed has a significant effect with p-value (0,000) < α (0,05) between physical activity value before and after intervention used audiovisual media it means audiovisual media was development worthy and can be used as an alternative media in improving physical activity.